Alembic - Jury, Sarah; Kaplinsky, Helen; Sames, Lucy A. (London : Res., 2018)
Breakdown, Uma ; Carpenter, Ele ; Shu Lea Cheang ; Clarke-Brown, Tamar ; Cooke, Kirsten ; Craven-Jones, Annabelle ; Doubal, Rosalie ; Hester, Helen ; Jury, Sarah ; Kaplinsky, Helen ; Moran, Stephanie ; Mputu, Elizabeth ; Roberts, Maggie ; Russell, Legacy ; Sames, Lucy A. ; Sin, Victoria ; Smith, Giulia ; Snowe, Megan ; Stupart, Linda ; Ayesha Tan Jones ; Wilding, Faith
boek